Modeling soil moisture‐precipitation feedback in the Sahel: Importance of spatial scale versus convective parameterization. Issue 23 (10th December 2013) - Taylor, Christopher M.; Birch, Cathryn E.; Parker, Douglas J.; Dixon, Nick; Guichard, Françoise; Nikulin, Grigory; Lister, Grenville M. S.
Abstract [1] Feedback between soil moisture and precipitation influence climate variability in semiarid regions. However, serious concerns exist about the ability of coarse‐scale global atmospheric models to depict one key aspect of the feedback loop, namely the sensitivity of daytime convection to soil moisture. Here we compare regional simulations using a single model, run at different spatial resolutions, and with convective parameterizations switched on or off against Sahelian observations. Convection‐permitting simulations at 4 and 12 km capture the observed relationships between soil moisture and convective triggering, emphasizing the importance of surface‐driven mesoscale dynamics. However, with the inclusion of the convection scheme at 12 km, the behavior of the model fundamentally alters, switching from negative to positive feedback. Similar positive feedback is found in 9 out of 10 Regional Climate Models run at 50 km. These results raise questions about the accuracy of the feedback in regional models based on current convective parameterizations.